Ultraviolet spectrophotometric determination of nitrate detecting nitrification rates and inhibition - Kelly, Richard T 2nd (Water environment research : a research publication of the Water Environment Federation, 2007)
Simple methods that rapidly detect nitrification inhibition are needed to enforce pretreatment programs and prevent upsets. The objective of this study was to demonstrate a rapid method for measuring nitrification inhibition by using nitrate generation rates (NGRs) coupled with direct UV detection of nitrate. The NGRs were measured with UV spectrophotometry at wavelengths between 225 and 240 nm, without chemical manipulation, and verified against ion chromatography. The method was shown to quickly and accurately measure nitrate concentrations after correcting for nitrite interference. Cadmium, hypochlorite and 1-chloro-2,4-dintrobenzene (CDNB) were tested for their ability to cause nitrification inhibition using this method. The CDNB was found to cause a correctable interference with the test, while hypochlorite provided an uncorrectable interference. Used as a batch method coupled with biotic and abiotic controls, this approach can be deployed at full-scale treatment plants as a relatively rapid (1.5 hours) means of identifying nitrification-inhibiting wastewaters